IMPLEMENTASI MEDIA SOSIAN DALAM PERKEMBANGAN ANAK USIA DINI (Studi Kasus di TK Kusuma Bangsa Dusun Gumul Kecamatan Pujon Kabupaten Malang) - Annisa Kurniasari; Ika Anggraheni; Mutiara Sari Dewi (UNISMA, 2022)
The use of internet technology in the current era of globalization is very influential on the life of every human being, especially in early childhood. PKK Kusuma Bangsa Pujon Kindergarten where parents who are the object of research have great concerns about their children in using gadgets, because it can be seen how the negative impact of the frequent use of gadgets is for children, but the birth of advanced technology such as gadgets also has many benefits for children if used properly to the child. This study uses a qualitative approach with case study research methods. In collecting data, data collection procedures were carried out through observation methods, observations by researchers of existing phenomena. In using digital technology media at PKK Kusuma Bangsa Pujon Kindergarten through the YouTube application, it becomes a solution as a means or medium for fine motor cognitive and physical development for children, and also has many other benefits, namely intellectual, emotional, spiritual and social intelligence of children.